2004
DOI: 10.1016/j.cub.2004.08.057
|View full text |Cite
|
Sign up to set email alerts
|

Vocal-Tract Filtering by Lingual Articulation in a Parrot

Abstract: Human speech and bird vocalization are complex communicative behaviors with notable similarities in development and underlying mechanisms. However, there is an important difference between humans and birds in the way vocal complexity is generally produced. Human speech originates from independent modulatory actions of a sound source, e.g., the vibrating vocal folds, and an acoustic filter, formed by the resonances of the vocal tract (formants). Modulation in bird vocalization, in contrast, is thought to origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 25 publications
0
44
0
2
Order By: Relevance
“…A high-low placement of the tongue changes the frequency of the first formant, and a front-back placement changes the frequency of the second formant. Although little is known about their importance in avian communication, formants or harmonic-rich formant-like structures are also observed in the vocalizations of various bird species, including zebra finches (Ohms et al, 2010), mynah birds (Klatt and Stefanski, 1974), African gray parrots (Pepperberg, 2010) and monk parakeets (Beckers et al, 2004;Ohms et al, 2012). The ability of mynah birds and parrots to modify formants contributes to their ability to imitate human speech, although the production mechanism may not be identical to that found in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-low placement of the tongue changes the frequency of the first formant, and a front-back placement changes the frequency of the second formant. Although little is known about their importance in avian communication, formants or harmonic-rich formant-like structures are also observed in the vocalizations of various bird species, including zebra finches (Ohms et al, 2010), mynah birds (Klatt and Stefanski, 1974), African gray parrots (Pepperberg, 2010) and monk parakeets (Beckers et al, 2004;Ohms et al, 2012). The ability of mynah birds and parrots to modify formants contributes to their ability to imitate human speech, although the production mechanism may not be identical to that found in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Research on speech-imitation by an African gray parrot has suggested that, similar to humans, the bird can change the front-back placement of the tongue to alter the formant properties of the vocalization, but not the high-low placement (Patterson and Pepperberg, 1994). In an experiment in which the syrinx of a euthanized monk parakeet was replaced with a speaker, Beckers et al (2004) found that artificially manipulating front-back tongue placement caused changes in formant frequency and amplitude, and manipulating high-low placement caused changes in amplitude. Ohms et al (2012) used Xray cineradiography to measure tongue height in naturally vocalizing monk parakeets.…”
Section: Introductionmentioning
confidence: 99%
“…A classic example from human speech is the source-filter theory for perceiving and classifying vowel sounds according to the frequency of their formants (Peterson and Barney, 1952), which are determined by resonance characteristics ('filtering') of the vocal tract. There is evidence that vocal tract filtering also plays an important role in vocal communication of other animals, although little is known about the mechanisms by which they are controlled (but see Hoese et al, 2000;Beckers et al, 2004).…”
mentioning
confidence: 99%
“…Estudos feitos com a caturrita, Myiopsitta monachus, mostraram ser suficiente que a língua se movimente uma fração de milímetro para articular sons tão distintos quanto um "a" ou "o" em inglês (Beckers et al, 2004). 37.…”
Section: Os Papagaios Demoníacosunclassified